Fatal Septic Shock in a Patient with Hemophagocytic Lymphohistiocytosis Associated with an Infectious Mononucleosis - Giorgio Berlot; Ariella Tomasini; Lorenzo Zandonà; Eugenio Leonardo; Rossana Bussani; Nadia Zarrillo (Case Reports in Critical Care)
The authors describe the case of a young woman who developed a clinical pictures resembling a septic shock-related multiple organ dysfunction syndrome a couple of months after having been diagnosed suffering from a hemophagocytic lymphohistiocytosis associated with an infectious mononucleosis. Despite the aggressive treatment, which included antibiotics, vasopressors, IV immunoglobulins, and the use of an extracorporeal device aimed to remove mediators released both during sepsis and the cytokine storm determined by the hemophagocytic lymphohistiocytosis, the patient died. At the autopsy, an extremely uncommon aggressive lymphoma of Epstein-Barr virus-positive T-lymphocytes with systemic involvement was discovered.